Analisis Penilaian Afektif Kemampuan Bernalar Kritis Ditinjau Dari Jenis Kelamin Peserta Didik di SMAN 5 Yogyakarta - Rumtini; Kasimin; Ease Arent; Abdul Jalil (Universitas Sarjanawiyata Tamansiswa, 2022)
An affective assessment of critical reasoning ability as a complex process involving data receiving-mastering, data analysis, and data evaluation, should be taught to students as the ability is vital in day-to-day life. The purpose of this study is to analyze the affective assessment of critical reasoning ability in terms of the gender of students in a Senior High School, SMAN 5, situated in Yogyakarta. The method used in this study is quantitative research. The subject involves 132 students at the 11th grade focusing on science and mathematics. Then, the independent t-test is utilized to analyze the data. The result indicated that the independent t-test obtained a significance value of 0.206 > 0.05, the mean of critical reasoning ability for female, 3.205, was greater than the male (3.085). However, it was considered insignificant as the gap was 1.120. The critical reasoning indicators such as searching for information, assessing, making conclusion, and making decision describe no significant difference based on gender. For further research, other factors can be analyzed in order to provide more implications for teachers in improving critical reasoning skills.